The Effects of Some Herb's Essential Oils on S. aureus in Feta Cheese - M Bonyadian; H Moshtaghi (Institue of Medicinal Plants, ACECR, 2007)
Background: This study was conducted to examine the effectiveness of some plant essential oils for control of growth and survival of S. aureus in pasteurized cheese.   Methods: Essential oils from Thyme (Thymus vulgaris), Tarragon (Artemisia dracunculus), caraway seed (Carum carvi), Penney royal (Mentha pulgium) and Peppermint (Mentha piperita) were extracted by Steam Distillation Method.   Two concentration close to the level of MIC for each essential oils (Thyme 0.1 and 0.2%, and the others 0.3 and 0.4%) were induced in samples and 10 6 CFU/g bacteria (S. aureus) was inoculated into the samples and controls.   All the samples and controls were kept at 12oC (The optimum temperature for ripening of cheese) for 168 h. Samples and controls were checked for the number of inoculated bacteria on 0, 24, 48, 72 and 168 h.   Results: The results of this study showed that the essential oils of these plants have antimicrobial activity on S. aureus, essential oils of the Thyme showed the most and for Tarragon the least antimicrobial activity on tested bacterium.   The Thyme oils caused 2 and 4 Log reduction of S. aureus to control at 0.1 and 0.2 % in cheese after 168 h. The essential oils of the Caraway seed, Penney royal and Peppermint had moderate effect on S. aureus and caused 1.5 and 2 Log reduction in the number of bacteria in the samples to controls.   The Tarragon oils caused 0.8 and 1.2 Log reduction to control at 0.3 and 0.4% after 168 h. Conclusion: From the results of this study it is concluded that essential oils of some plants may use as a natural preservative in some foods.